Qualitative Interview with Older Adults and Caregivers on their Perspectives with Self-Management and Remote Vital Sign Monitoring. - Chan, Carissa S.Y.; Park, Sarah; Yakubu, Titilola; Jafari, Nooshin; Ho, Kendall (Canadian Geriatrics Journal, 2025)
Background: Research underscores the role of self-management capabilities as a strategy for enhancing the well-being of older adults by mitigating potential health risks and functional decline. Self-management tools like remote vital sign monitoring serve as critical indicators for detecting adverse health outcomes. Thus, the study aims to understand prior experiences of older adults and caregivers in self-management, along with soliciting their perspective on the technical advantages and barriers of using technology in medicine, citing their experience with remote vital sign monitoring as an example. Methods: Through semi-structured qualitative interviews, 32 participants were interviewed virtually about their personal experience with prior remote vital sign monitoring. Eligibility included older adults and/or caregivers of older adults. Participants who were unable to read or understand English were excluded, unless sufficient support was provided to navigate the study procedures. Results: The full interview transcriptions were captured under the following five major themes: health-care experience, personal perception of technology in medicine, impact of remote vital sign monitoring, contactless monitoring system considerations, and acceptance and collaboration in remote vital sign measurement. Conclusion: Based on participants' prior experience using remote vital sign monitoring, compatibility, data security and privacy, and patient education were identified as important considerations when developing monitoring systems for older adults and caregivers.